Increase in the skewness of extratropical vertical velocities with climate warming: fully nonlinear simulations versus moist baroclinic instability. (27th December 2017) - O'Gorman, Paul A.; Merlis, Timothy M.; Singh, Martin S.
Abstract : The distribution of vertical velocities in the extratropical troposphere is skewed such that upward motions are faster than downward motions. This skewness is important for the intensity distribution of precipitation and for the effective static stability experienced by moist eddies. We show here that the skewness of the vertical velocity increases in magnitude as the climate warms in simulations with an idealized general circulation model (GCM), except in very warm climates. That the skewness increases with warming is consistent with studies of moist baroclinic instability which suggest that the area of updraughts should contract as the stratification approaches moist neutrality in warm climates. However, the increase in skewness with warming is much weaker in the fully nonlinear simulations as compared to what is found for unstable modes of moist baroclinic instability in the same GCM. Nonlinear equilibration to a macroturbulent state leads to a reduction in skewness in warm climates. Therefore, while the unstable modes may be relevant for some cases of cyclogenesis, they overestimate the effect of warming on the skewness of the overall distribution of the vertical velocity. Remarkably, the most unstable mode transitions from a quasi‐periodic wave to an isolated diabatic Rossby vortex at sufficiently high temperatures, with possible implications for fast‐growing disturbances in warm climates. Abstract : Snapshots of instantaneous vertical velocity (red is upward) are shown at a mid‐tropospheric level in simulations with an idealized GCM. As the climate warms, the vertical velocity becomes more skewed, with faster upward velocities than downward velocities. The increase in skewness with climate warming is weaker for the fully nonlinear simulations (left) as opposed to the most unstable modes of moist baroclinic instability (right).